Underground Life : Or, Mines and Miners - Simonin, Louis; Bristow, H. W. (Place of publication not identified : publisher not identified, 1869)
Born in Marseilles, Louis Simonin (1830-86) became a leading mining engineer of his age. He travelled widely on government and private commissions, particularly around the United States, where he was held in very high esteem. His posthumous renown rests primarily on this substantial work on mining, first published in 1867. The book is divided into three parts, dealing with coal mining, metal mining, and the mining of precious stones. It covers metallurgy and mineralogy, the history of mining, and techniques, methods and equipment. Bringing the struggles of miners to life, and enhanced by numerous illustrations by some of the leading engravers of the day, the book is regarded as having inspired and informed Émile Zola, whose great novel Germinal (1885) depicts coal miners' lives during a strike. Simonin's work reached a wide readership in his native France, and this English translation appeared in 1869.
Title from publisher's bibliographic system (viewed on 07 Mar 2017).